Evaluation of some plant secondary metabolites activity to control algae - Mohammed, Safa Khalid; M.Jawad, Abdul latif (Iraqi Journal of Science, 2021)
This study includes isolation , purification and identification of algae from differentaquatic environments in Baghdad.Two different plant species belonging to different families were selected which wereCitrilluscolocynthus and Cordiamyxa for their fruits and fruits samples respectively.Crude extracts were extracted from each plant and their antialgal activity wereevaluated.Different concentrations (5,15,25) mg/ml of these extracts were preparedand their antagonistic activity was studied, and the resulted inhibition effects in ( %)of concentration of chlorophyll(a) after 12 days was evaluated.Results showed that Chloroccumhumicola was the most sensitive to these extracts.However, Anabaena circinalis was less sensitive than all other algae used in thisstudy. Also showed that phenol was the most active against algae and terpene hadless antagonistic activity comparing with all other extracts.